PENGARUH TATA KELOLA PERUSAHAAN, UMUR PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP MANAJEMEN LABA - ERIKA VERIANA; SANTOSO CHANDRA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence regarding the factors that influence earnings management. These factors are board size, leverage, audit quality, audit committee size, audit committee independence, ownership structure, firm size, firm age and firm growth. This research used a population of manufacuring companies listed on the Indonesia Stock Exchange (BEI) for the period 2017-2019. The sample used in the research was 69 companies, which were selected using a purposive sampling method. The hypothesis in this research used the multiple regression analysis method by applying The Modified Jones Model as a measure of earnings management. The results of this research indicate that the variable audit quality, firm age, and firm growth have an influence on earnings management. Meanwhile, variables board size, leverage, audit committee size, audit committee independence, ownership structure, and firm size have no influence on earnings management